Establishment of an acute arterial mesenteric ischaemia model in canines with an endovascular approach - Shi, Yadong; Zhou, Yangyi; Yuan, Yuan; Kong, Jie; Gong, Maofeng; Chen, Liang; He, Xu; Su, Haobo; Gu, Jianping (Frontiers in Veterinary Science, 2024)
Purpose: This study aimed to evaluate the feasibility of establishing an arterial acute mesenteric ischemia (AMI) model in canines using transcatheter autologous thrombus administration. Material and methods: Ten canines were divided into the experimental group (Group A, n = 5) and the sham group (Group B, n = 5). The canines in Group A received thrombus administration to the superior mesenteric artery (SMA) through a guiding catheter, while the canines in Group B received normal saline administration. Blood samples were collected and tested at baseline and 2 hours after modelling. Canines in Group A underwent manual thromboaspiration after blood and intestine samples were collected. Ischaemic grades of intestinal mucosa were evaluated under light microscopes. Results: The AMI models were successfully conducted in all canines without procedure-related vessel injury or death. At the 2-hour follow-up, the high-sensitivity C-reactive protein and D-dimer in Group A were significantly higher than in Group B (5.72 ± 1.8 mg/L vs 2.82 ± 1.5 mg/L, p = .024; 2.25 ± 0.8 μg/mL vs 0.27 ± 0.10 μg/mL, p = .005; respectively). The mean histopathologic intestinal ischaemic grade in Group A was significantly higher than in Group B (2.4 ± 0.5 vs 0.8 ± 0.4, p < .001). After a median of 2 times of thromboaspiration, 80% (4/5) of the canines achieved complete SMA revascularisation. Conclusion: This experimental study demonstrated that establishing an arterial model in canines using endovascular approaches was feasible. The present model may play an important role in the investigation of endovascular techniques in the treatment of arterial AMI.